Penatalaksanaan Guided Imagery Terhadap Nyeri Pada Pasien Post Rekonstruksi Lumbal 5 - Maharani, Anita, Dewi Suryandari, S.Kep., Ns., M.Kep (2017)
Background : Fracture is a fracture, characterized by a condition in which bone tissue connection or unity disconnected. Fractures are usually caused by trauma, fall or accident. Lumbar fracture is a fracture that occurs in the lumbar vertebrae section. The manifestation of this condition is the presence of pain in the hip area. Pain is an uncomfortable feeling and subjective nature where only people who can feel pain. There are different ways to treat pain or actions both pharmacological and non-pharmacological measures. One of the actions to be undertaken nurses ie non-pharmacological measures which can help patients to eliminate or reduce pain is to act guided imagery. Purpose : The writing of scientific publications is that writers can do and determine the impact of actions guided imagery for pain in patients Ms. R with post reconstruction Lumbar 5 lumbar with implant failure in Ward Parang Seling Orthopedic Hospital Prof. Dr. R. Soeharso Surakarta. Methods : Descriptive study approach is to perform nursing care in patients with post-reconstruction with implant failure Lumbar 5 lumbar beginning of assessment, intervention, implementation and evaluation of nursing. Results : After nursing actions during 3x24 hours are expected to decrease the patient's pain scale decreased the original 5 to 2. Conclusion : Based on research conducted found that guided imagery relaxation technique is one of the non-pharmacological pain management methods are effective for reducing pain and not cause harmful side effects. Suggestion : It is expected that the action that has been done to the patient's author could be a reference to commit acts of management of pain in patients with lumbar fracture and can be used as a reference for the next writer to make a report on pain containment procedures using other techniques of pain management in patients with lumbar fracture.